The effectiveness of the EU’s rule of law conditionality mechanism: Theoretical observations based on the case of Hungary - Czina, Veronika (Intersections. East European Journal of Society and Politics, 2024)
The effectiveness of post-accession conditionality within the EU has been of pivotal importance for the EU in past years. The European Union has plenty of tools for monitoring the compliance of EU Member States; however, when it comes to enforcement mechanisms, EU institutions perform poorly. Respect for the rule of law is especially crucial in this regard, as certain Member States (i.e. Poland and Hungary) have committed violations in this area. Hungary has been subject to several infringement procedures due to failure to comply with EU law, and the Article 7 procedure has even been activated against it. In 2020, the EU decided to connect rule-of-law violations to the EU budget disbursement by introducing the rule-of-law conditionality mechanism, which was launched against Hungary in 2022. This paper evaluates this conditionality mechanism through the example of Hungary and assesses whether it is more effective than the previous tools used to address rogue Member State behaviour and prevent continuous rule-of-law violations on a national level.